Aplicación de un sistema de costos por órdenes de producción para la productora de lácteos nueva esperanza de la provincia de Pichincha, cantón Mejía, parroquía de Alóag - Vaca Padilla, Johanna Patricia (2015)
This research dealt with the application of a Cost System for Production Orders for Dairy Production "NUEVA ESPERANZA" located in Alóag. The methodology used for the study was descriptive research and deductive - inductive, analytical and structural methods was possible to apply techniques and data collection instruments such as interview and survey for the situation analysis and interpretation in which was the producer, giving solution to with the system design based on the specific needs of the company and reaching the system implementation costs, it allowed the development of formats, economic activities kept and procedures to collect admitted….